2004
DOI: 10.1017/s1355770x04001718
|View full text |Cite
|
Sign up to set email alerts
|

Environmental values and resource management options: a choice modelling experience in Malaysia

Abstract: The management of the Matang Mangrove Wetlands in Perak State, Malaysia is under review. To assist decision makers in determining the optimal management strategy, a choice modelling application was undertaken to estimate the non-market values provided under different management options. Implicit prices for environmental attributes including the area of environmental forest protected, the number of bird species protected and the recreation use of the area were estimated. In addition, the implicit price of a soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 12 publications
5
53
0
5
Order By: Relevance
“…Several other studies also found positive relationship between these variables. For example, positive impact of income on WTP is witnessed in studies by Westerberg et al, 2010;Ghosh and Mondal, 2012;Birol et al, 2006;Othman et al, 2004;Birol et al, 2011;Hanley et al, 2006;Oglethorpe and Miliadou, 2000;Bliem et al, 2012 andNuva et al, 2011.The positive effect of membership in NGO on WTP also reported by Oglethorpe and Miliadou 2000;Pattison et al 2011. The negative interaction between number of people per household with the level 3 of natural scenery indicates that large families have lower WTP compare to small size families. Our results were similar to some other previous studies (Perez-Verdin et al, 2011;Hammitt et al, 2001;Pattison et al, 2011).…”
Section: Results Of the Choice Experimentsmentioning
confidence: 93%
“…Several other studies also found positive relationship between these variables. For example, positive impact of income on WTP is witnessed in studies by Westerberg et al, 2010;Ghosh and Mondal, 2012;Birol et al, 2006;Othman et al, 2004;Birol et al, 2011;Hanley et al, 2006;Oglethorpe and Miliadou, 2000;Bliem et al, 2012 andNuva et al, 2011.The positive effect of membership in NGO on WTP also reported by Oglethorpe and Miliadou 2000;Pattison et al 2011. The negative interaction between number of people per household with the level 3 of natural scenery indicates that large families have lower WTP compare to small size families. Our results were similar to some other previous studies (Perez-Verdin et al, 2011;Hammitt et al, 2001;Pattison et al, 2011).…”
Section: Results Of the Choice Experimentsmentioning
confidence: 93%
“…34 See, for example Randall (1994) on the travel cost method and Day et al (2007) on the hedonic pricing method. 35 The stated preference literature is vast but for a few examples focussed upon ecosystem services Naylor and Drew (1998), Banzhaf et al (2006), Carlsson et al (2003), Othman et al (2004), Hanley et al (2003), Hearne and Salinas (2002), Huybers and Bennett (2003), Mansfield et al (2008), Naidoo and Wiktor (2005), Rolfe et al (2000). 36 Notice that we deliberately eschew the term 'intrinsic value'.…”
Section: Valuing Ecosystem Servicesmentioning
confidence: 99%
“…Provides unique and aesthetic landscape, suitable habitat for diverse fauna and flora Tourism, recreation, education, and research Creel and Loomis (1992), Bergstrom and Stoll (1993), Cooper and Loomis (1993), King and Lester (1995), Bateman and Langford (1997), Hammitt et al (2001), Johnston et al (2002), Carlsson et al (2003), Othman et al (2004), Brouwer and Bateman (2005), Birol et al (2006), Birol and Cox (2007), Do and Bennet (2008), Jenkins et al (2010).…”
Section: Maintenance Of Temperature Precipitationmentioning
confidence: 99%
“…Various examples include: balancing agricultural conversion with riverine wetland conservation in South Africa (Jogo and Hassan 2010); managing environmental change in the Norfolk and Suffolk Broads of the UK (Turner et al 2004); comparing flood control regimes to natural floodplain production in Bangladesh (Islam and Braden 2006); examining rural land-use changes and floodplain management scenarios in the UK (Posthumus et al 2010); valuing changes in ecosystem services from various wetland management regimes in Greece (Birol et al 2006); evaluating preferences for alternative restoration options for the Greater Everglades ecosystem in the USA (Milon and Scrogin 2006); valuing ecosystem services from wetlands restoration in the Mississippi Valley, USA (Jenkins et al 2010); and assessing different mangrove management options in Malaysia (Othman et al 2004).…”
Section: Final Remarksmentioning
confidence: 99%